Metagenomic insights to understand transient influence of Yamuna River on taxonomic and functional aspects of bacterial and archaeal communities of River Ganges - Samson, Rachel; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Rajput, Vinay; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Science of the Total Environment, 2019)
River confluences are interesting ecosystems to investigate for their microbial community structure and functional potentials. River Ganges is one of the most important and holy river of India with great mythological history and religious significance. The Yamuna River meets Ganges at the Prayagraj (formerly known as Allahabad), India to form a unique confluence. The influence of Yamuna River on taxonomic and functional aspects of microbiome at this confluence and its downstream, remains unexplored. To unveil this dearth, whole metagenome sequencing of the microbial (bacterial and archaeal) community from the sediment samples of December 2017 sampling expedition was executed using high throughput MinION technology. Results revealed differences in the relative abundance of bacterial and archaeal communities across the confluence. Grouped by the confluence, a higher abundance of Proteobacteria and lower abundance of Bacteroidetes and Firnacutes was observed for Yamuna River (G15Y) and at immediate downstream of confluence of Ganges (G15DS), as compared to the upstream, confluence, and farther downstream of confluence. A similar trend was observed for archaeal communities with a higher abundance of Euryarchaeoto in G15Y and G15DS, indicating Yamuna River's influence. Functional gene(s) analysis revealed the influence of Yamuna River on xenobiotic degradation, resistance to toxic compounds, and antibiotic resistance interceded by the autochthonous microbes at the confluence and succeeding downstream locations. Overall, similar taxonomic and functional profiles of microbial communities before confluence (upstream of Ganges) and farther downstream of confluence, suggested a transient influence of Yamuna River. Our study is significant since it may be foundational basis to understand impact of Yamuna River and also rare event of mass bathing on the microbiome of River Ganges. Further investigation would be required to understand, the underlying cause behind the restoration of microbial profiles post-confluence farther zone, to unravel the rejuvenation aspects of this unique ecosystem. (C) 2019 Elsevier B.A. All rights reserved.
Keywords: Confluence zone; Ganges; Metagenomics; Transient influence; Yamuna

Comprehensive metagenomic insights into a unique mass gathering and bathing event reveals transient influence on a riverine ecosystem - Yadav, Rakeshkumar; Rajput, Vinay; Gohil, Kushal; Khairnar, Krishna; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
The religious mass gathering and bathing can pose a multitude of significant public health challenges and lead to severe alterations in the river microbial ecology. The Pandharpur Wari is an annual pilgrimage of Maharashtra, India, where millions of devotees carry the footprints of the saint-poets and pay their obeisance to Lord Vitthal on the 11th day of moon's waxing phase (Ashadi Ekadashi). As a part of the ritual, the engrossed devotees, walk over 250 km, take a first holy dip in a sacred river Indrayani at Alandi and secondly in Bhima River at Pandharpur. The MinION-based shotgun metagenomic approach was employed to examine the impact of spiritual mass bathing on environmental changes (concerning the river microbial community structure and functions); and public health aspects (in terms of changes in the pathogenic potential and antibiotic resistance). The analysis of bathing and post-bathing samples of both the rivers revealed alterations in the alpha and beta diversity, indicating significant spatiotemporal variations in the overall microbial structure and function. Furthermore, the analysis revealed up to 80% of differences in the abundance of virulence genes between the bathing and post bathing samples. We observed parallel increase of priority skin and enteric pathogens (ranging from 11% to 80%) such as Acinetobacter baumannii, Staphylococcus aureus, Streptococcus pyogenes, Mycobacterium tuberculosis, and Pseudomonas aeruginosa during the bathing event. Moreover, we observed a significant increase in the antibiotic resistance in the bathing samples of Bhima and Indrayani rivers respectively. Altogether, this is the first comprehensive metagenomic study unravelling the influence of religious mass-bathing on the riverine ecosystem.
Keywords: Antibiotic resistance; Mass bathing; MinION sequencing; Priority pathogens; Virulence genes

Deciphering taxonomic and functional diversity of fungi as potential bioindicators within confluence stretch of Ganges and Yamuna Rivers, impacted by anthropogenic activities - Samson, Rachel; Rajput, Vinay; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Chemosphere, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">River confluences are interesting ecological niche with limited information in respect of the structure and the functions of diverse microbial communities. Fungi are gaining global attention as promising biological spectacles for defining the trophic status of riverine systems. We condense existing knowledge in confluence diversity in two Indian rivers (i.e. Ganges and Yamuna), by combining sediment metagenomics using long read aided MinION nanopore sequencing. A total of 63 OTU’s were observed, of which top 20 OTU’s were considered based on relative abundance of each OTU at a particular location. Fungal genera such as <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus, Penicillium<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Kluveromyces, Lodderomyces,<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Nakaseomyces<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> were deciphered as potential bio indicators of river pollution and eutrophication in the confluent zone. <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In silico<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> functional gene analysis uncovered hits for neurodegenerative diseases and xenobiotic degradation potential, supporting bioindication of river pollution in wake of anthropogenic intervention.

Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Pan-genomics of Ochrobactrum species from clinical and environmental origins reveals distinct populations and possible links - Gohil, Kushal; Rajput, Vinay; Dharne, Mahesh (Genomics, 2020)
Ochrobactrum genus is comprised of soil-dwelling Gram-negative bacteria mainly reported for bioremediation of toxic compounds. Since last few years, mainly two species of this genus, O. intermedium and O. anthropi were documented for causing infections mostly in the immunocompromised patients. Despite such ubiquitous presence, study of adaptation in various niches is still lacking. Thus, to gain insights into the niche adaptation strategies, pan-genome analysis was carried out by comparing 67 genome sequences belonging to Ochrobactrum species. Pan-genome analysis revealed it is an open pan-genome indicative of the continuously evolving nature of the genus. The presence/absence of gene clusters also illustrated the unique presence of antibiotic efflux transporter genes and type IV secretion system genes in the clinical strains while the genes of solvent resistance and exporter pumps in the environmental strains. A phylogenomic investigation based on 75 core genes depicted better and robust phylogenetic resolution and topology than the 16S rRNA gene. To support the pan-genome analysis, individual genomes were also investigated for the mobile genetic elements (MGE), antibiotic resistance genes (ARG), metal resistance genes (MRG) and virulence factors (VF). The analysis revealed the presence of MGE, ARG, and MRG in all the strains which play an important role in the species evolution which is in agreement with the pan-genome analysis. The average nucleotide identity (ANI) based on the genetic relatedness between the Ochrobactrum species indicated a distinction between individual species. Interestingly, the ANI tool was able to classify the Ochrobactrum genomes to the species level which were assigned till the genus level on the NCBI database.
Keywords: Antibiotic resistance; Average nucleotide identity; Clinical and environmental strains; Core genes; MinION; Virulence factors

Shotgun metagenome guided exploration of anthropogenically driven resistomic hotspots within Lonar soda lake of India - Chakraborty, Jaya; Sapkale, Vibhavari; Rajput, Vinay; Shah, Manan; Kamble, Sanjay; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
Anthropogenic activities mediated antibiotic resistance genes (ARGs) in the pristine aquatic bodies (lakes) is raising concern worldwide. Long read shotgun sequencing was used to assess taxonomic diversity, distribution of ARGs and metal resistance genes (MRGs) and mobile genetic elements (MGEs) in six sites within hypersaline Lonar soda lake (India) prone to various anthropogenic activities. Proteobacteria and Euryarchaeota were dominant phyla under domain Bacteria and Archaea respectively. Higher abundance of Bacteroidetes was pragmatic at sites 18LN5 and 18LN6. Functional analysis indicated 26 broad-spectrum ARGs types, not reported earlier in this ecosystem. Abundant ARG types identified were multidrug efflux, glycopepetide, bacitracin, tetracycline and aminogylcoside resistance. Sites 18LN1 and 18LN5 depicted 167 and 160 different ARGs subtypes respectively and rpoB2, bcrA, tetA(48), mupA, ompR, patA, vanR and multidrug ABC transporter genes were present in all samples. The rpoB2 gene was dominant in 18LN1, whereas bcrA gene in 18LN2-18LN6 sites. Around 24 MRGs types were detected with higher abundance of arsenic in 18LN1 and copper in 18LN2-18LN6, signifying metal contamination linked to MRGs. The bacterial taxa Pseudomonas, Thioalkalivibrio, Burkholderia, Clostridium, Paenibacillus, Bacillus and Streptomyces were significantly associated with ARGs. This study highlights the resistomic hotspots in the lake for deploying policies for conservation efforts.
Keywords: ARGs; diversity; Lonar lake; MGEs; MRGs; Nanopore sequencing

Functional metagenomic landscape of polluted river reveals potential genes involved in degradation of xenobiotic pollutants - Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh (Environmental Research, 2021)
Rapid industrialization contributes substantially to xenobiotic pollutants in rivers. As a result, most of the rivers traversing urban settlements are in significantly deteriorated conditions. These pollutants are recalcitrant, requiring robust catabolic machinery for their complete transformation into bioavailable and non-toxic byproducts. Microbes are versatile dwellers that could adapt to such contaminants by using them as a source of nutrients during growth. However, efficient bioremediation requires an in-depth knowledge of microbial diversity and their metabolism related genes in the polluted niches. We employed MinION shotgun sequencing, to comprehend the biodegradation related genes and their function potential operating in the polluted urban riverine system of Western India. A vast number of catabolic genes were detected for the xenobiotic pollutants such as Benzoate, Nitrotoluene, Aminobenzoate, Drug metabolism, and Polycyclic Aromatic Hydrocarbons. Aerobic, and anaerobic catabolism genes, were mapped for their ability of degradation of xenobiotics. Interestingly, catabolism profiles of multiple aromatic compounds culminated into the Benzoate degradation pathway, suggesting it as a plausible central pathway for the autochthonous bacterial communities. Further mapping with RemeDB database, predicted plastic and dye degrading enzymes. Moreover, the diversity indices for the pollutant degrading enzymes suggested little variations (R-2 value of 18%) between the city and non-city (outskirts of city limits) riverine stretch indicating the impact of industrialization in the outskirts of the city stretch as well. Altogether, this study would serve as a preliminary baseline for future explorations concerning river cleaning programs and also exploiting such microbes for bioremediation applications.
Keywords: Benzoate; Bioremediation; MinION; Riverine system; Xenobiotics

Metagenomic analysis of a mega-city river network reveals microbial compositional heterogeneity among urban and peri-urban river stretch - Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh (Science of the Total Environment, 2021)
The rivers in the megacities face a constant inflow of extremely polluted wastewaters from various sources, and their influence on the connected peri-urban river is still poorly understood. The riverine system in Pune consists of Rivers Mula, Ramnadi, Pawana, Mutha, and Mula-Mutha, traversing through the urban settlements of Pune before joining River Bhima in the peri-urban region. We used MinION-based metagenomic sequencing to generate a comprehensive understanding of the microbial diversity differ-ences between the urban and peri-urban zones, which has not been explored at the meta scale until date. The taxonomic analysis revealed significant enrichment of pollution indicators microbial taxa (Welsch's t-test, p < 0.05, Benjamini-Hochberg FDR test) such as Bacteriodetes, Firmicutes, Spirochaetes, Synergistetes, Euryarcheota in the urban waters as compared to peri-urban waters. Further, the peri-urban waters showed a significantly higher prevalence of ammonium oxidising archaeal groups such as Nitrososphaeraceae (Student's t-test p-value <0.05 with FDR correction), thereby probably suggesting the influence of agricultural runoffs. Besides, the microbial community diversity assessment also indicated the significant dissimilarity in the microbial community of urban and peri-urban waters. Overall, the analysis predicted 295 virulence genes mapping to 38 different path-ogenic bacteria in the riverine system. Moreover, the higher genome coverage (at least 60%) for priority patho-gens such as Pseudomonas, Klebsiella, Acinetobacter, Escherichia, Aeromonas in the sediment metagenome consolidates their dominance in this riverine system. To conclude, our investigation showed that the unre-strained anthropogenic and related activities could potentially contribute to the overall dismal conditions and in-fluence the connected riverine stretches on the outskirts of the city . (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Industrialisation; Peri-urban; Riverine system; Urbanisation; Virulence factors

Metagenomic analysis reveals genetic insights on biogeochemical cycling, xenobiotic degradation, and stress resistance in mudflat microbiome - Mohapatra, Madhusmita; Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh S.; Rastogi, Gurdeep (Journal of Environmental Management, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Mudflats are highly productive coastal ecosystems that are dominated by halophytic vegetation. In this study, the mudflat sediment microbiome was investigated from Nalabana Island, located in a brackish water coastal wetland of India; Chilika, based on the MinION shotgun metagenomic analysis. Bacterial, archaeal, and fungal communities were mostly composed of Proteobacteria (38.3%), Actinobacteria (20.7%), Euryarchaeota (76.1%), Candidatus Bathyarchaeota (6.8%), Ascomycota (47.2%), and Basidiomycota (22.0%). Bacterial and archaeal community composition differed significantly between vegetated mudflat and un-vegetated bulk sediments. Carbon, nitrogen, sulfur metabolisms, oxidative phosphorylation, and xenobiotic biodegradation were the most common microbial functionalities in the mudflat metagenomes. Furthermore, genes involved in oxidative stresses, osmotolerance, secondary metabolite synthesis, and extracellular polymeric substance synthesis revealed adaptive mechanisms of the microbiome in mudflat habitat. Mudflat metagenome also revealed genes involved in the plant growth and development, suggesting that microbial communities could aid halophytic vegetation by providing tolerance to the abiotic stresses in a harsh mudflat environment. Canonical correspondence analysis and co-occurrence network revealed that both biotic (vegetation and microbial interactions) and abiotic factors played important role in shaping the mudflat microbiome composition. Among abiotic factors, pH accounted for the highest variance (20.10%) followed by available phosphorus (19.73%), total organic carbon (9.94%), salinity (8.28%), sediment texture (sand) (6.37%) and available nitrogen (5.53%) in the mudflat microbial communities. Overall, this first metagenomic study provided a comprehensive insight on the community structure, potential ecological interactions, and genetic potential of the mudflat microbiome in context to the cycling of organic matter, xenobiotic biodegradation, stress resistance, and in providing the ecological fitness to halophytes. These ecosystem services of the mudflat microbiome must be considered in the conservation and management plan of coastal wetlands. This study also advanced our understanding of fungal diversity which is understudied from the coastal lagoon ecosystems.

Metagenomic exploration reveals a differential patterning of antibiotic resistance genes in urban and peri-urban stretches of a riverine system - Rajput, Vinay; Yadav, Rakeshkumar; Dharne, Mahesh S. (Environmental Science and Pollution Research, 2021)
{Antimicrobial resistance in the riverine ecosystem of urban areas is an alarming concern worldwide, indicating the importance of molecular monitoring to understand their patterning in urban and peri-urban areas. In the present study, we evaluated the influence of urban rivers on the connected peri-urban rivers of a riverine system of India in the context of antibiotic resistance genes. The rivers traversing through urban (Mula, Mutha, Pawana, and Ramnadi) and peri-urban stretches (Bhima and Indrayani) form the riverine system of Pune district in Maharashtra, India. The MinION-based shotgun metagenomic analysis revealed the resistome against 26 classes of antibiotics, including the last line of antibiotics. In total, we observed 278 ARG subtypes conferring resistance against multiple drugs (40%), bacitracin (10%), aminoglycoside (7.5%), tetracycline (7%), and glycopeptide (5%). Further, the alpha diversity analysis suggested relatively higher ARG diversity in the urban stretches than peri-urban stretches of the riverine system. The NMDS (non-metric multidimensional scaling) analysis revealed significant differences with overlapping similarities (stress value = 0.14
Keywords: Antibiotic resistance; MinION; Peri-urban rivers; Urbanization

Spatio-temporal resolution of taxonomic and functional microbiome of Lonar soda lake of India reveals metabolic potential for bioremediation - Chakraborty, Jaya; Rajput, Vinay; Sapkale, Vibhavari; Kamble, Sanjay; Dharne, Mahesh (Chemosphere, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Lonar Lake, India; a hypersaline and hyperalkaline extremophilic ecosystem having a unique microbial population has been rarely explored for bioremediation aspects. MinION-based shotgun sequencing was used to comprehensively compare the microbial diversity and functional potential of xenobiotic degradation pathways with seasonal changes. Proteobacteria and Firmicutes were prevalent bacterial phyla in the pre-monsoon and post-monsoon samples. Functional analysis from SEED-subsystem and KEGG database revealed 28 subsystems and 18 metabolic pathways for the metabolism of aromatic compounds and xenobiotic biodegradation respectively. Occurrence of N-phenyl alkanoic, benzoate, biphenyl, chloroaromatic, naphthalene, and phenol degradation genes depicted varied abundance in the pre-monsoon and post-monsoon samples. Further, KEGG analysis indicated nitrotoluene degradation pathway (ko00633) abundant in post-monsoon samples, and the benzoate degradation pathway (ko00362) predominant in 19LN4S (pre-monsoon) than 18LN7S (post-monsoon) samples. The abundant genes for benzoate degradation were pcaI: 3-oxoadipate CoA-transferase, alpha subunit, pcaH: protocatechuate 3,4-dioxygenase, beta subunit, and pcaB: 3-carboxy-cis, cis-muconate cycloisomerase, and 4-oxalocrotonate tautomerase. This metagenomic study provides a unique blueprint of hitherto unexplored xenobiotic biodegradation genes/pathways in terms of seasonal variations in the Lonar Lake, and warrants active exploitation of microbes for bioremediation purposes.

Gut microbiota dysbiosis in patients with intracranial sino-venous thrombosis and acute ischemic stroke in the young - Prabhu, Varsha A.; Rajput, Vinay; Yadav, Rakeshkumar; Gohil, Kushal; Dharne, Mahesh S.; Unnikrishnan, Mazhuvancherry Kesavan; Gorthi, Sankar Prasad (Annals of Indian Academy of Neurology, 2022)

High throughput sequencing based direct detection of SARS-CoV-2 fragments in wastewater of Pune, West India - Dharmadhikari, Tanmay; Rajput, Vinay; Yadav, Rakeshkumar; Boargaonkar, Radhika; Patil, Dhawal; Kale, Saurabh; Kamble, Sanjay P.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2022)
Given a large number of SARS-CoV-2 infected individuals, clinical detection has proved challenging. The wastewater-based epidemiological paradigm would cover the clinically escaped asymptomatic individuals owing to the faecal shedding of the virus. We hypothesised using wastewater as a valuable resource for analysing SARS-CoV-2 mutations circulating in the wastewater of Pune region (Maharashtra; India), one of the most affected during the covid-19 pandemic. We conducted study in open wastewater drains from December 2020- March 2021 to assess the presence of SARS-CoV-2 nucleic acid and further detect mutations using ARTIC protocol of MinION sequencing. The analysis revealed 108 mutations across six samples categorised into 39 types of mutations. We report the occurrence of mutations associated with Delta variant lineage in March-2021 samples, simultaneously also reported as a Variant of Concern (VoC) responsible for the rapid increase in infections. The study also revealed four mutations; S:N801, S:C480R, NSP14:C279F and NSP3:L550del not currently reported from wastewater or clinical data in India but reported worldwide. Further, a novel mutation NSP13:G206F mapping to NSP13 region was observed from wastewater. Notably, S:P1140del mutation was detected in December 2020 samples while it was reported in February 2021 from clinical data, indicating the instrumentality of wastewater data in early detection. This is the first study in India to demonstrate utility of sequencing in wastewater based epidemiology to identify mutations associated with SARS-CoV-2 virus fragments from wastewater as an early warning indicator system. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: ARTIC protocol; Epidemiology; Metagenomics; Nanopore sequencing; SARS-CoV-2; wastewater

Metagenomic mining of Indian river confluence reveal functional microbial community with lignocelluloytic potential - Rajput, Vinay; Samson, Rachel; Yadav, Rakeshkumar; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (3 Biotech, 2022)
Microbial carbohydrate-active enzymes (CAZyme) can be harnessed for valorization of Lignocellulosic biomass (LCB) to value-added chemicals/products. The two Indian Rivers Ganges and the Yamuna having different origins and flow, face accumulation of carbon-rich substrates due to the discharge of wastewater from adjoining paper and pulp industries, which could potentially contribute to the natural enrichment of LCB utilizing genes, especially at their confluence. We analyzed CAZyme diversity in metagenomic datasets across the sacred confluence of the Rivers Ganges and Yamuna. Functional annotation using CAZyme database identified a total of 77,815 putative genes with functional domains involved in the catalysis of carbohydrate degradation or synthesis of glycosidic bonds. The metagenomic analysis detected similar to 41% CAZymes catalyzing the hydrolysis of lignocellulosic biomass polymers- cellulose, hemicellulose, lignin, and pectin. The Beta diversity analysis suggested higher CAZyme diversity at downstream region of the river confluence, which could be useful niche for culture-based studies. Taxonomic origin for CAZymes revealed the predominance of bacteria (97%), followed by archaea (1.67%), Eukaryota (0.63%), and viruses (0.7%). Metagenome guided CAZyme diversity of the microflora spanning across the confluence of Ganges-Yamuna River, could be harnessed for biomass and bioenergy applications.
Keywords: CAZymes; Confluence (Sangam); Lignocellulosic; River Ganges; River Yamuna

Genomic surveillance reveals early detection and transition of delta to omicron lineages of SARS-CoV-2 variants in wastewater treatment plants of Pune, India - Rajput, Vinay; Pramanik, Rinka; Malik, Vinita; Yadav, Rakeshkumar; Samson, Rachel; Kadam, Pradnya; Bhalerao, Unnati; Tupekar, Manisha; Deshpande, Dipti; Shah, Priyanki; Shashidhara, L. S.; Boargaonkar, Radhika; et al. (Environmental Science and Pollution Research, 2023)
The COVID-19 pandemic has emphasized the urgency for rapid public health surveillance methods to detect and monitor the transmission of infectious diseases. The wastewater-based epidemiology (WBE) has emerged as a promising tool for proactive analysis and quantification of infectious pathogens within a population before clinical cases emerge. In the present study, we aimed to assess the trend and dynamics of SARS-CoV-2 variants using a longitudinal approach. Our objective included early detection and monitoring of these variants to enhance our understanding of their prevalence and potential impact. To achieve our goals, we conducted real-time quantitative polymerase chain reaction (RT-qPCR) and Illumina sequencing on 442 wastewater (WW) samples collected from 10 sewage treatment plants (STPs) in Pune city, India, spanning from November 2021 to April 2022. Our comprehensive analysis identified 426 distinct lineages representing 17 highly transmissible variants of SARS-CoV-2. Notably, fragments of Omicron variant were detected in WW samples prior to its first clinical detection in Botswana. Furthermore, we observed highly contagious sub-lineages of the Omicron variant, including BA.1 (similar to 28%), BA.1.X (1.0-72%), BA.2 (1.0-18%), BA.2.X (1.0-97.4%) BA.2.12 (0.8-0.25%), BA.2.38 (0.8-1.0%), BA.2.75 (0.01-0.02%), BA.3 (0.09-6.3%), BA.4 (0.24-0.29%), and XBB (0.01-21.83%), with varying prevalence rates. Overall, the present study demonstrated the practicality of WBE in the early detection of SARS-CoV-2 variants, which could help track future outbreaks of SARS-CoV-2. Such approaches could be implicated in monitoring infectious agents before they appear in clinical cases.
Keywords: Bioinformatics pipeline; COVID-19; Early warning; India; Next-generation sequencing; Omicron; Public health; SARS-CoV-2; wastewater; Wastewater-based epidemiology

Spatio-temporal variation of the microbiome and resistome repertoire along an anthropogenically dynamic segment of the Ganges River, India - Samson, Rachel; Rajput, Vinay; Yadav, Rakeshkumar; Shah, Manan; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (Science of the Total Environment, 2023)
Aquatic ecosystems are regarded as a hub of antibiotic and metal resistance genes. River Ganges is a unique riverine system in India with socio-cultural and economic significance. However, it remains underexplored for its microbiome and associated resistomes along its anthropogenically impacted course. The present study utilized a nanopore sequenc-ing approach to depict the microbial community structure in the sediments of the river Ganges harboring antibiotic and metal resistance genes (A/MRGs) in lower stretches known for anthropogenic impact. Comprehensive microbiome analyses revealed resistance genes against 23 different types of metals and 28 classes of antibiotics. The most dominant ARG category was multidrug resistance, while the most prevalent MRGs conferred resistance against copper and zinc. Seasonal differences dismally affected the microbiota of the Ganges. However, resistance genes for fosmidomycin and tetracycline varied with season ANOVA, p < 0.05. Interestingly, 333 and 334 ARG subtypes were observed at all the locations in pre-monsoon and post-monsoon, respectively. The taxa associated with the dominant ARGs and MRGs were Pseudomonas and Burkholderia, which are important nosocomial pathogens. A substantial phage diversity for pathogenic and putrefying bacteria at all locations attracts attention for its use to tackle the dissemination of antibiotic and metal-resistant bacteria. This study suggests the accumulation of antibiotics and metals as the driving force for the emergence of resistance genes and the affiliated bacteria trafficking them. The present metagenomic as-sessment highlights the need for comprehensive, long-term biological and physicochemical monitoring and mitigation strategies toward the contaminants associated with ARGs and MRGs in this nationally important river.
Keywords: Antibiotics (ARGs); Bacteriophages; Heavy metals (MRGs); Metagenomics; Microbiome; River Ganges

Early detection of KP.2 SARS-CoV-2 variant using wastewater-based genomic surveillance in Pune, Maharashtra, India - Rajput, Vinay; Das, Rashmita; Pramanik, Rinka; Nannaware, Kiran; Sushma, Y.; Taji, Nyabom; Rajput, Vishal; Rajkhowa, Riyakshi; Pacharne, Poonam; Shah, Priyanki; Gogate, Niharika; Sangwar, Poornima; et al. (Journal of Travel Medicine, 2024)

Genome sequencing and protein modeling unraveled the 2AP biosynthesis in Bacillus cereus DB25 - Dhondge, Harshal V.; Barvkar, Vitthal T.; Dastager, Syed G.; Dharne, Mahesh S.; Rajput, Vinay; Pable, Anupama A.; Henry, Robert J.; Nadaf, Altafhusain B. (International Journal of Food Microbiology, 2024)
2-Acetyl-1-pyrroline (2AP) is an important and major flavor aroma compound responsible for the fragrance of basmati rice, cheese, wine, and several other food products. Biosynthesis of 2AP in aromatic rice and a few other plant species is associated with a recessive Betaine aldehyde dehydrogenase 2 (BADH2) gene. However, the literature is scant on the relationship between the functional BADH2 gene and 2AP biosynthesis in prokaryotic systems. Therefore, in the present study, we aimed to explore the functionality of the BADH2 gene for 2AP biosynthesis in 2AP synthesizing rice rhizobacterial isolate Bacillus cereus DB25 isolated from the rhizosphere of basmati rice (Oryza sativa L.). Full-length BcBADH2 sequence was obtained through whole genome sequencing (WGS) and further confirmed through traditional PCR and Sanger sequencing. Then the functionality of the BcBADH2 gene was evaluated in-silico through bioinformatics analysis and protein docking studies and further experimentally validated through enzyme assay. The sequencing and bioinformatics analysis results revealed a full-length 1485 bp BcBADH2 coding sequence without any deletion or premature stop codons. Full-length BcBADH2 was found to encode a fully functional protein of 54.08 kDa with pI of 5.22 and showed the presence of the conserved amino acids responsible for enzyme activity. The docking studies confirmed a good affinity between the protein and its substrate whereas the presence of BcBADH2 enzyme activity confirmed the functionality of BADH2 enzyme in B. cereus DB25. In conclusion, the findings of the present study suggest that B. cereus DB25 is able to synthesize 2AP despite a functional BADH2 gene and there may be a different molecular mechanism responsible for 2AP biosynthesis in bacterial systems, unlike that found in aromatic rice and other eukaryotic plant species.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice flavor; Betaine aldehyde dehydrogenase 2; Protein-ligand docking; Rhizobacteria; Whole-genome sequence

Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.

Long-term genomic surveillance of SARS-CoV-2 in campus wastewater depicts lineage trends and public health implications during and after omicron waves - Pramanik, Rinka; Rajput, Vinay; Malik, Vinita; Nannaware, Kiran; Matra, Sejal; Joshi, Sai; Kumar, Shubham; Samson, Rachel; Yadav, Rakesh Kumar; Shah, Priyanki; Shashidhara, LS; Dastager, Syed; et al. (Environment & Health, 2025)
SARS-CoV-2 transmission and detection on academic campuses in low- to middle-income countries has not been explored. The present study explored wastewater surveillance of SARS-CoV-2 in a campus setting in Pune, Maharashtra, India, offering insights into variant-specific trends and their correlation with clinical cases over a 2.5 year period from November 2021 to April 2024. We collected 242 wastewater samples from the campus sewershed and processed them to extract RNA and perform RT-qPCR and sequencing, followed by lineage assignment using the LCS tool. Early signals of different SARS-CoV-2 variants, such as BA.2.X, JN.1.X, and KP.2.X, were detected in wastewater prior to its first clinical report in Maharashtra, India. Wastewater viral load strongly correlated with clinical cases during the Omicron phase (ρ = 0.73–0.81) compared to the post-Omicron phase (ρ = −0.06 to 0.31). This study also highlights that alerts and warnings issued on the basis of wastewater viral hikes have proven instrumental in preventing outbreaks of SARS-CoV-2 variants on campus. However, downgrading COVID-19 from pandemic status by the WHO resulted in a subsequent decrease in public vigilance, changing the viral dynamic in the last phase of the study. This study showcases the utility of wastewater surveillance in a campus setting as an early warning system and understands the interplay of public health policy effects in viral dynamics within controlled ecosystems, such as campuses or offices.